BIG DATA DAN KINERJA PERUSAHAAN: SUATU KAJIAN DENGAN PENDEKATAN ANALISIS BIBLIOGRAFI - Kusumarita, Anna; Ngatno, Ngatno; Wijayanto, Andi (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2025)
The literature related to the impact of big data on company performance is still fragmented and lacks integrating the results of current studies. This study uses a systematic literature review method. The analysis process uses 73 articles from Scopus. The purpose of this study is to contribute to the literature related to the relationship between big data and company performance. This study provides a systematic overview of how big data affects various types of company performance (financial, operational, ESG, technology & innovation, and marketing). This systematic review is proposed to pave the way for conceptual and empirical research streams by emphasizing the importance of big data analytics in improving company performance. In addition, this observation offers academics and practitioners a better understanding of the relationship between big data analytics and company performance.